2011
DOI: 10.1037/a0025013
|View full text |Cite
|
Sign up to set email alerts
|

Stepping back to see the big picture: When obstacles elicit global processing.

Abstract: Can obstacles prompt people to look at the "big picture" and open up their minds? Do the cognitive effects of obstacles extend beyond the tasks with which they interfere? These questions were addressed in 6 studies involving both physical and nonphysical obstacles and different measures of global versus local processing styles. Perceptual scope increased after participants solved anagrams in the presence, rather than the absence, of an auditory obstacle (random words played in the background; Study 1), particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 131 publications
5
58
0
1
Order By: Relevance
“…Indeed, any skilled activity depends upon the existence of some constraints (Csikszentmihalyi 1997;Marquc et al 2011), and human performance generally suffers in the face of too many options. In jewellery making, constraints are imposed by the materials being used, the tools, the design brief, aesthetic considerations, historical considerations and so on.…”
Section: Creativity In Dynamic Systemsmentioning
confidence: 99%
“…Indeed, any skilled activity depends upon the existence of some constraints (Csikszentmihalyi 1997;Marquc et al 2011), and human performance generally suffers in the face of too many options. In jewellery making, constraints are imposed by the materials being used, the tools, the design brief, aesthetic considerations, historical considerations and so on.…”
Section: Creativity In Dynamic Systemsmentioning
confidence: 99%
“…Studies have shown that people perform better at a given task when an obstacle is in their way [23], and constraints may allow people to clarify and focus on the task at hand [19]. This can already be observed to a certain degree in the cost-interaction hypothesis [2], for examplewith increased querying costs leading to stickier results [33].…”
Section: Introductionmentioning
confidence: 79%
“…We believe that categorization flexibility is one such factor. Marguc, Förster, and van Kleef (2011) indicate that categorizing broadly is associated with integrative, global processing. We argue that high categorization flexibility consumers, when confronted with difficult-to-justify hedonic options due to the self-control challenge they pose, process information about the options in a global, multi-dimensional manner.…”
Section: Prohedonic Effect Of Categorization Flexibilitymentioning
confidence: 97%